MENUJU MODERNISASI PENDIDIKAN ISLAM - Hartono Hartono (Universitas Muhammadiyah Tangerang, 2019)
This study wass a theoretical basis for the analysis of modernization carried out by the world of Islamic education, especially in Indonesia. For this purpose, the study was distributed into three sub-chapters. The first sub-chapter discussed a historical review of the modernization of Islamic education. The second discussed the modernization of Islamic education in Indonesia. The last discussion was directed at disclosing the response of Muslims to modern education